2009
DOI: 10.1002/bsl.857
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions and their implications in criminal responsibility

Abstract: For over 200 years, Western courts have considered pleas of "not guilty by reason of insanity" (NGRI) for defendants in possession of a mental defect rendering them unable to understand the wrongfulness of their act. Until recently, determining the mental state of a defendant has fallen largely upon the shoulders of court psychologists and experts in psychiatry for qualitative assessments related to NGRI pleas and mitigation at sentencing. However, advances in neuroscience--particularly neurological scanning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…The issue of whether or not fMRI evidence has substantial probative value is beyond the scope of this paper, but it well addressed elsewhere (e.g., Feigenson, 2006;Dressing, Sartorius, & Meyer-Lindenberg, 2008;Sinnott-Armstrong et al, 2008). Some legal decisions have concluded that the admission of brain imaging evidence in a criminal trial would be more prejudicial than probative (see Batts, 2009), though others have suggested that if the technology reaches accuracy rates greater than 90%, its admission is inevitable (Rosen, 2007).…”
Section: Weighing the Probative Value Of Fmri Evidencementioning
confidence: 96%
“…The issue of whether or not fMRI evidence has substantial probative value is beyond the scope of this paper, but it well addressed elsewhere (e.g., Feigenson, 2006;Dressing, Sartorius, & Meyer-Lindenberg, 2008;Sinnott-Armstrong et al, 2008). Some legal decisions have concluded that the admission of brain imaging evidence in a criminal trial would be more prejudicial than probative (see Batts, 2009), though others have suggested that if the technology reaches accuracy rates greater than 90%, its admission is inevitable (Rosen, 2007).…”
Section: Weighing the Probative Value Of Fmri Evidencementioning
confidence: 96%
“…This concern is that, when jurors are able to "see" the source of behavior in the image of a malfunctioning brain, they will be substantially more persuaded than they have been by traditional forms of testimony such as behavioral descriptions by lay or expert witnesses or explanations of the behavior offered by psychological and psychiatric experts (Batts, 2009;Brown & Murphy, 2010;Dumit, 1999;Gurley & Marcus, 2008;Rose, 2000;Roskies, 2008).…”
mentioning
confidence: 98%
“…In theory, most would agree that behaviors caused by defined brain lesions or abnormalities are not under the control of the individual and thus cannot be called acts or considered as an expression of moral agency. But in practice, brain lesions or other abnormalities often do not prove a lack of understanding the wrongness of a certain act at the time of commission (Batts 2009). Neither does it prove an absent ability to act according to one's insight, which would justify a diminished or missing criminal responsibility in most European countries.…”
Section: Conceptual Issues Of Moral Agencymentioning
confidence: 98%